Genotype-guided dietary supplementation in precision nutrition - Gkouskou, K. K.; Grammatikopoulou, M. G.; Vlastos, I.; Sanoudou, D.; Eliopoulos, A. G. (Nutr RevNutr RevNutr Rev, 2020)
Achieving adequate micronutrient status, while avoiding deficiencies, represents a challenge for people globally. Consequently, many individuals resort to oral nutrient supplementation (ONS) in order to correct suboptimal dietary intakes. Advances in the fields of nutrigenetics and nutritional genomics have identified differences in response to micronutrient supplementation according to genetic makeup, adding dietary supplement use to the clinician's toolkit in the precision nutrition era. This review focuses on published evidence linking genetic variants to the responses associated with some of the most popular dietary supplements. With an increasing number of health professionals becoming involved in the prescription of ONS, identifying and matching individuals to the appropriate dietary supplement according to their genotype is important for achieving optimal health benefits and micronutrient equilibrium, while reducing the adverse events and financial costs often associated with excessive ONS.